IN SILICO ANALYSIS OF STREPTOMYCES SP SECONDARY METABOLITE 1, 2- BENZENEDICARBOXYLIC ACID, MONO (2-ETHYLHEXYL) ESTER WITH ESBL PROTEINS - LOKESH RAVI,; SUBASHINI E JASMINE,; KANNABIRAN KRISHNAN,; GOPIESH KHANNA V, (International Journal of Pharma and Bio Sciences, 2015)
The anti-ESBL activity of 1, 2-benzenedicarboxylic acid, mono (2-ethylhexyl) ester (DMEHE) extracted from marine Streptomyces sp strain VITSJK8 was further confirmed by in silico analysis. A total of 10 ESBL proteins was chosen for this study from the protein data bank (PDB) and were docked with the DMEHE. The resultant atomic contact energy (ACE) was compared with dockings of known antibiotic ertapenem, penicillin G, amoxicillin, rocephin and cefozopran. PatchDock online docking server was utilized for docking studies. LigPlot+ and PyMOL were used to evaluate the docking results obtained from PatchDock. The docking of DMEHE with ESBL proteins showed the ACE value range from -198.42 to 22.62, while docking of ertapenem showed the ACE value range from -217.67 to -71.8. DMEHE formed hydrogen bonds with AMPC, CTXM-9, TEM-1 and TEM-52 ESBL proteins. The interaction between DMEHE and ESBL protein complex was unstable and no covalent bond formation was observed, whereas ertapenem and ESBL complex was highly stable because of the covalent bond and hydrogen bond formation in the ligand-protein interaction. Similarly penicillin G, amoxicillin, rocephin and cefozopran also demonstrated higher stability with ESBL proteins compared to DMEHE. Based on this study, it could be concluded that bacterial proteins will not involve in lysis of DMEHE and therefore DMEHE would be an effective drug for treating the drug resistant ESBL pathogens.